2022
DOI: 10.3390/molecules27031060
|View full text |Cite
|
Sign up to set email alerts
|

Bis-Amiridines as Acetylcholinesterase and Butyrylcholinesterase Inhibitors: N-Functionalization Determines the Multitarget Anti-Alzheimer’s Activity Profile

Abstract: Using two ways of functionalizing amiridine—acylation with chloroacetic acid chloride and reaction with thiophosgene—we have synthesized new homobivalent bis-amiridines joined by two different spacers—bis-N-acyl-alkylene (3) and bis-N-thiourea-alkylene (5) —as potential multifunctional agents for the treatment of Alzheimer’s disease (AD). All compounds exhibited high inhibitory activity against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) with selectivity for BChE. These new agents displayed ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 121 publications
(156 reference statements)
0
11
0
Order By: Relevance
“…Providing efficient tools for various QSPR and QSAR problems [ 64 , 65 , 66 ], this approach has been successfully employed to model the structure influence on various pharmacokinetic, toxicity, and physico-chemical endpoints such as human intestinal absorption [ 67 ], blood–brain barrier permeability [ 68 , 69 ], hERG-mediated cardiac toxicity [ 70 ], lipophilicity [ 71 ], etc. Some of these models are available online at our ADMET Prediction Service page ( accessed on 1 December 2022) and have been successfully used to evaluate the key absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties of diverse potential drug compounds in virtual screening and molecular design studies [ 72 , 73 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Providing efficient tools for various QSPR and QSAR problems [ 64 , 65 , 66 ], this approach has been successfully employed to model the structure influence on various pharmacokinetic, toxicity, and physico-chemical endpoints such as human intestinal absorption [ 67 ], blood–brain barrier permeability [ 68 , 69 ], hERG-mediated cardiac toxicity [ 70 ], lipophilicity [ 71 ], etc. Some of these models are available online at our ADMET Prediction Service page ( accessed on 1 December 2022) and have been successfully used to evaluate the key absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties of diverse potential drug compounds in virtual screening and molecular design studies [ 72 , 73 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The estimated pK a value of the amiridine fragment [37,71] suggests that both protonated and noncharged forms could coexist in a solution at the experimental pH. Thus, molecular docking was performed for both forms of the ligands.…”
Section: Molecular Modeling Studiesmentioning
confidence: 99%
“…[27,31,32] This has led to an intensive search for compounds exhibiting dual activity: as AChE inhibitors and as inhibitors of Aβ aggregation, that is, these types of compounds can simultaneously improve cognitive function and have a diseasemodifying effect. [13,14,31,[33][34][35][36][37] BChE is also involved in the formation and/or maturation of Aβ plaques. [38][39][40] It was shown that BChE is associated with various stages and aspects of amyloidogenesis, including a production [19,[41][42][43] and toxicity of aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations